Study on the regulation of renal tubular cell apoptosis by SIRT1/NF-κB signaling pathway in septic acute kidney injury - Weiwei Chu; Xuedong Sun; Yihe Yan (Renal Failure)
SIRT1 regulates gene transcription via various signaling pathways, mitigating oxidative stress damage in renal tubular epithelial cells, reducing renal inflammation, and decreasing apoptosis in tubular cells. This study explores the mechanisms of action of SIRT1 in sepsis-induced acute kidney injury (AKI), offering a theoretical foundation for future treatments. Experiments were carried out in a CLP mouse model and an in vitro model using LPS-stimulated HK-2 cells. Immunoblotting and ELISA were employed to assess the expression levels of inflammatory cytokines (p < 0.01), finding that SIRT1 effectively reduces the inflammatory response in sepsis-induced AKI. Moreover, the detection of cell apoptosis via multiple pathways showed that SIRT1 can reduce the rate of cell apoptosis and effectively decrease oxidative stress in the validation reaction. Transmission electron microscopy observations further supported these findings, demonstrating that SIRT1 expression induces the blockade of cell apoptosis processes. The biochemical experiments concluded that SIRT1 ameliorates sepsis-induced AKI. Consequently, SIRT1 may represent a novel therapeutic target for AKI.